Lorraine Code (Ed.) (2003). Feminist Interpretations of Hans-Georg Gadamer (Hans-Georg Gadamerin Feminist Yorumları) (407 sayfa)The University Park: Pennsylvania State University Press. ISBN: 0271022442. - Ulukütük, Mehmet (My University, 2011)
…
Keywords: Sosyoloji